Design and experimental study of the fertilizer applicator with vertical spiral fluted rollers - Wang, Yu; Tan, Yipeng; Wei, Silong; Liao, Mingming; Zang, Ying; Zeng, Shan (International Journal of Agricultural and Biological Engineering, 2023)
To improve the uniformity and accuracy of fertilizing amount for fertilizer applicators with spiral fluted roller, this paper experimentally studied the influence of major structural parameters on the fertilizing performance. Through two sets of orthogonal tests, it is found that the helix angle and installation angle of spiral fluted rollers are the main factors, which affect the uniformity of fertilizer discharge and the linear relationship between fertilizing amount and opening, respectively. Based on these findings, the experiment and analysis were carried out to determine the optimal helix angle and installation angle for the spiral fluted roller The experimental results of fertilizing performance show that: when the helix angle is 45°, it able to achieve satisfactory uniformity of fertilizer discharge and linear relationship between fertilizing amount and rotational speed; when the installation angle is 40°, it enhances the accuracy of fertilizer discharge with good linear relationship between fertilizing amount and opening. Compared with the fertilizing performance of traditional fertilizer applicators with horizontally installed straight fluted roller, in the aspect of uniformity, the optimized fertilizer applicators reduce the variation coefficient of fertilizing amount within 0.2 s at low speed (10-30 r/min) from 5.1%-52.5% to 4.2%-14.7%; in the aspect of accuracy; and increase the correlation coefficient square R2 between fertilizing amount and opening from 0.93-0.97 to no less than 0.996, and the regression intercept in the fitting equation is reduced from larger than 10.0 to less than 1.0.Keywords: fertilizer applicator, spiral fluted roller, helix angle, orthogonal testDOI: 10.25165/j.ijabe.20231605.7555Citation: Wang Y, Tan Y P, Wei S L, Liao M M, Zang Y, Zeng S. Design and experimental study of the fertilizer applicator with vertical spiral fluted rollers. Int J Agric & Biol Eng, 2023; 16(5): 80–87.